RESTRUCTURING AND REFORM IN THE JIU VALLEY - MIHAELA CAMELIA SCHMIDT; FELICIA ANDRIONI (Annals of the University of Petrosani: Economics)
The article provides an analysis of the restructuring and reform process in the Jiu Valley mining in the context of national reforms.